Estudantes brasileiros e colombianos de ciências sociais: percepções sobre raça, ações afirmativas e currículo - Conceição, Iberê Araujo da (2021)
The Third World Conference against Racism, held in Durban in South Africa and organized by UNESCO in 2001, was an important milestone for the struggles of the peoples of the African Diaspora in the Americas, which stimulated the adoption of Affirmative Action policies for black people. In this perspective, this dissertation sought to identify whether the increase in the presence of black students in higher education opened or not the possibility of a process of curricular decolonization. Our focus was on two courses, Social Sciences in Brazil and Sociology in Colombia. The methodology used was qualitative, through the analysis of the documents of Pedagogical Political Projects, menus and teaching plans between 2001 and 2018, as well as the application of in-depth interviews with four black students from two important universities in both countries. The results indicated that, first, there is an incipient approach to the theme of ethnic-racial relations in the curriculum of both courses, limited to the optional subjects, however, we observe an opening to the theme a little greater in Brazil. Second, there were convergences in the impacts of Affirmative Actions on the identity shifts experienced by students, at the time of access to higher education, which reflect on family dynamics, especially with regard to ethnic-racial belonging and educational opportunities. Third, we identified that participations in student collectives, research and extension groups, as well as the influence of the RAP culture, have fundamental roles for the parallel formation of students and, for the most part, helped to build the theoretical-political position and the students' ethnic-racial belonging. Fourth, the students' perceptions, for the most part, associated the absence of disciplines on the themes with racism present in the academy, also pointing out the predominance of a Eurocentric bias in the curricula and a desire for curricular change towards a model that contemplates other matrices of thought and recognize the black population from its historical agency. The difference between the two countries can be explained by the difference in the size of the black population in both countries, the difference between the Colombian ethnic model and the Brazilian racial Affirmative Action. In addition, the absence of black teachers and researchers on ethnic-racial issues creates an unfavorable scenario for curricular change at both universities.